Practice makes perfect Italian conversation - Danesi, Marcel 1946- (New York McGraw-Hill, 2023)
Learn to speak Italian as fluently as Italians do—an indispensable guide, now with a timely new chapter on remote communication Whether you're learning Italian now at an intermediate level or looking to brush up on your Italian conversational skills, Practice Makes Perfect: Italian Conversation offers a unique and effective way to learn to speak the language fluently and spontaneously. You'll get a handle on sentence building right away, through extensive exercises that let you practice what you've learned through engaging dialogues and numerous real-life examples. Based on the successful approach of the Practice Makes Perfect series, Practice Makes Perfect: Italian Conversation, Premium Third Edition is organized around 11 units that present specific conversational functions, from Striking Up a Conversation to Giving Opinions, each exemplified with short dialogues that are also available as audio recordings via app. The units provide you the opportunity not simply to converse, but to build and support your knowledge of the language with essential instruction on correct pronunciation, grammar, syntax and word usage. Proven approach to learning helps you get a handle on Italian conversation right away, and build on your learnings as you go Supported by audio recordings, via app, of all 60 dialogues, plus numerous exercise answers 850 exercise questions help you practice what you've learned through dialogues and practical examples A special conversational "markers" table in the index shows important elements of conversation that have no exact equivalents in English NEW: Includes a timely chapter on remote communication (video conferencing).
Text in English and Italian.
Keywords: Italian language -- Conversation and phrase books -- English; Italian language -- Textbooks for foreign speakers -- English; Italian language -- Grammar -- Problems, exercises, etc